Anti-keratin antibodies in rheumatoid arthritis. - Young, B J (1979)
A naturally occurring antibody that reacts with the keratinised tissue of animal oesophagus was found in the serum of 75 out of 129 patients (58%) with classical or definite rheumatoid arthritis (RA) but not in sera from 105 healthy people. Detection of the antibody, which is unrelated to rheumatoid factor, is more specific for RA than the reaction in the sheep-cell agglutination test but less sensitive.